Mutations in the Voltage Sensors of Domains I and II of Nav1.5 that are Associated with Arrhythmias and Dilated Cardiomyopathy Generate Gating Pore Currents - Moreau, Adrien; Gosselin-Badaroudine, Pascal; Boutjdir, Mohamed; Chahine, Mohamed (Frontiers in Pharmacology, 2015)
Voltage gated sodium channels (Nav) are transmembrane proteins responsible for action potential initiation. Mutations mainly located in the voltage sensor domain (VSD) of Nav1.5, the cardiac sodium channel, have been associated with the development of arrhythmias combined with dilated cardiomyopathy. Gating pore currents have been observed with three unrelated mutations associated with similar clinical phenotypes. However, gating pores have never been associated with mutations outside the first domain of Nav1.5. The aim of this study was to explore the possibility that gating pore currents might be caused by the Nav1.5 R225P and R814W mutations (R3, S4 in DI and DII, respectively), which are associated with rhythm disturbances and dilated cardiomyopathy. Nav1.5 WT and mutant channels were transiently expressed in tsA201 cells. The biophysical properties of the alpha pore currents and the presence of gating pore currents were investigated using the patch-clamp technique. We confirmed the previously reported gain of function of the alpha pores of the mutant channels, which mainly consisted of increased window currents mostly caused by shifts in the voltage dependence of activation. We also observed gating pore currents associated with the R225P and R814W mutations. This novel permeation pathway was open under depolarized conditions and remained temporarily open at hyperpolarized potentials after depolarization periods. Gating pore currents could represent a molecular basis for the development of uncommon electrical abnormalities and changes in cardiac morphology. We propose that this biophysical defect be routinely evaluated in the case of Nav1.5 mutations on the VSD.